The Implementation of ASLUT Program in Handling Neglected Ederly - Salmah, Sri; Chulaifah, Chulaifah (Jurnal Penelitian Kesejahteraan Sosial, 2018)
The goal of this research is to know the implementation of neglected ederly assistant (ASLUT), in Luwu District, South celebes Province, and its benefit to receiver. This research is qualitative-descriptive. Data were gathered through interview with implementators of ASLUT and local social agency officials, four social guides, post officers, and several elderlies as receivers of the program, plus documentary analysis, observation and focus group discussion. Data were analysis through qualitative-descriptive technique. The result showed that the implementation of the program gave 40 receivers with right criteria, four of them were bed-ridden that any time need assistance by other people, 13 of them living with their families, 13 of them living with other people, and 10 of them living alone. The proses ang its target had been implemented rightly. The assistance was implementad through giving Rp 200.000,- received three monthly per person and can be used to buy daily needs that before was held by their family or environmental people. The success of the program can not be forgoten from the role of four social guides and postmen as assistance outreach to benefisal people. It recommended that the sum of the assistance and social guides should be incremented to maximize the program.